Enhancing Renewable Energy Utilization in Remote Areas Through an Accessible IoT Monitoring Framework: A Case Study on Tidung Island - Nadhiroh, Nuha; Setiana, Hatib; Muchlishah; Monika, Dezetty; Wardhani, Rika Novita; Dwiyaniti, Murie; Isdawimah, Isdawimah; Tahazen, Tahazen (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2025)
This research addresses the lack of an accurate and efficient monitoring system for renewable energy utilization in Tidung Island. Despite its high solar and wind energy potential, the absence of real-time environmental data hinders optimal energy management. Existing IoT-based monitoring systems are costly and complex, making them unsuitable for remote areas. This research integrates Blynk IoT and Google Sheets database for real-time, cost-effective, and easily accessible data storage. This system enables real-time data acquisition to support efficient energy management and environmental monitoring in remote areas. Testing results show that the Telkomsel 4G modem provides a more stable connection with lower latency and minimal packet loss. Temperature remains between 25–30°C, while humidity fluctuates up to 100% at night. Wind speed is classified as low to moderate (1.0–6.1 m/s), and CO₂ levels range from 400–600 PPM, remaining within safe limits. These findings suggest the need for improved energy storage, system resilience against environmental changes, and adaptive energy management strategies for optimal hybrid renewable energy utilization.